High-mobility group protein B1 (HMGB1) level in plasma of alcohol use disorder patients in withdrawal state - Anna S. Tolmacheva; Daria V. Bobrik; Mark M. Melamud; Ilia S. Efremov; Georgy A. Nevinsky; Valentina N. Buneva; Elvina A. Akhmetova; Azat R. Asadullin; Evgeny A. Ermakov (Middle East Current Psychiatry)
Abstract Background Alcohol use disorder (AUD) and alcohol withdrawal syndrome (AWS) are known to be accompanied by inflammatory processes caused by the toxic effects of alcohol and cell death. High-mobility group protein B1 (HMGB1) is one of the molecules released during cell death called alarmins, but the concentration of this protein in the blood of AWS patients has not been studied. This study aims to investigate plasma HMGB1 concentration in AWS patients compared with healthy individuals and to search for clinical associations with HMGB1 levels. Methods A total of 70 male patients with AWS and 44 male healthy subjects were included in the study. Blood sampling and clinical evaluation were performed on day 5 after hospitalization and AWS development, but after resolution of the most severe withdrawal symptoms. HMGB1 concentration was determined by enzyme-linked immunosorbent assay. Results Median HMGB1 concentration in AWS patients (8.48 (6.29, 11.39) ng/mL) was fourfold higher compared with healthy subjects (2.16 (0.86, 3.93) ng/mL). HMGB1 showed good diagnostic potential as a predictor of AWS patients and healthy subjects (AUC, 0.95; 95% CI, 0.91–0.98; p < 0.0001) with a sensitivity of 0.93 and a specificity of 0.80. Remarkably, HMGB1 level did not change in patients with comorbid alcoholic liver disease and did not depend on AWS severity and other clinical characteristics of patients. Only elevated HMGB1 level was found in patients who failed finger-nose test indicating an association with neurologic impairment. HMGB1 concentration was also increased in patients with subthreshold insomnia compared to patients without insomnia assessed by the Insomnia Severity Index questionnaire. Elevated HMGB1 level was found in patients with evidence of high level of inflammation as also confirmed by the correlation of HMGB1 with inflammatory markers. Conclusion Increased HMGB1 indicates activation of inflammatory processes in AUD patients with AWS. HMGB1 can be considered a promising inflammatory biomarker of AWS. The association of HMGB1 with neurological impairments and insomnia requires further investigation.